THE EFFECT OF THE PHENOMENON OF NOMOPHOBIA, PHUBBING, AND FOMO ON SOCIAL INTELLIGENCE OF HIGH CLASS STUDENTS OF SD NEGERI KANIGARAN I PROBOLINGGO CITY - Indah Febria Chasanah; Lilik Sri Hariani; Cicilia Ika Rahayu Nita; Indah Febria Chasanah1 (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
The pervasive use of digital devices among elementary school students has given rise to emerging digital phenomena such as Nomophobia, Phubbing, and Fear of Missing Out (FoMO), which are presumed to influence children’s social intelligence. This study aims to examine the impact of these three variables on the social intelligence of upper-grade students at SDN Kanigaran 1, Probolinggo. Employing a quantitative explanatory causal approach, data were collected through a Likert-scale questionnaire from a purposive sample of 172 students in grades IV to VI. The data were analyzed using multiple linear regression via SPSS version 31. Findings reveal that Nomophobia, Phubbing, and FoMO collectively exert a statistically significant effect on social intelligence. Partially, Phubbing and FoMO showed significant effects, whereas Nomophobia did not. These results suggest that emotional dependency on digital devices does not inherently hinder children’s social intelligence, particularly when external regulation by teachers and parents remains strong. Conversely, Phubbing the tendency to ignore real-life interactions in favor of device use and FoMO, characterized by anxiety over missing digital content, were found to detrimentally affect students’ capacity for social engagement. This study underscores the urgent need for digital literacy education and the early cultivation of social skills to ensure a balanced development between digital interaction and authentic social experience.